A rare case of sarcoidosis involving the middle turbinates: an incidental diagnosis - Tosun Emine; Erbek Selim S; Erbek Seyra; Cakmak Ozcan (BMC, 2006)
Abstract Background Sarcoidosis is a chronic, systemic granulomatous disease of unknown etiology that features noncaseating granulomas in many body regions. Sinonasal involvement is rare but is also suspected to be underreported. Case presentation We present the case of a 39-year-old woman who was incidentally diagnosed with isolated sarcoidosis involving the middle turbinates. Histopathologic examination of resected concha bullosa material and an extensive panel of diagnostic tests revealed a diagnosis of isolated sarcoidosis. Since no systemic manifestations were detected, topical corticosteroid (nasal spray) was administered in the postoperative period. Throughout the 12 months after surgery, the patient remained free of symptoms and all nasal endoscopy examinations were normal. Conclusion Although isolated nasal involvement of sarcoidosis is rare, otorhinolaryngologists should consider this condition in a differential diagnosis for sinonasal complaints.